Sistem Pembayaran Sekolah Menggunakan Metode Rapid Application Development (RAD) - Ferdiansyah; Dian Hartanti; Srisulistiowati, Dwi Budi; Rejeki, Sri (Program Studi Informatika, Fakultas Ilmu Komputer Universitas Bhayangkara Jakarta Raya, 2023)
Al-Azhar Jaya Indonesia Integrated Islamic School is one of the educational institutions that has elementary and junior high school levels. So far, the school payment system has not been integrated into the system. This causes errors in the process of recording data and making reports. The purpose of this research is to build an integrated school payment system so that it can facilitate the administration in carrying out their duties. The development method uses Rapid Application Development (RAD). making applications using the TypeScript and SqLite programming languages with the Visual Studio framework as a text editor. The results of this study can be implemented in the form of a school payment system application.